Recent Advances in Monte Carlo Methods (IntechOpen, 2024)
Monte Carlo methods, or Monte Carlo experiments, are a broad class of computational algorithms that rely on repeated random sampling to obtain numerical results. This book provides a comprehensive overview of these methods, discussing their fundamental aspects and their applications in solving a large array of problems. Recent Advances in Monte Carlo Methods is a useful reference for scholars, researchers, and students in pure and applied mathematics, physical sciences, engineering and technology, computer science, numerical analysis, scientific computing, and the general sciences.